A post harvest handling system for cassava (Manihot esculenta, Crantz) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The cassava root, like the other root and tuber crops, has been traditionally treated as a hardy crop with little attention being paid to proper harvesting and post harvest handling procedures. These reasons have accounted for the major losses in the marketing chain. This root is more difficult to handle than other tropical roots as it has an intrinsic short shelf-life of two (2) to three (3) days. The flesh deteriorates into the characteristic blue black discolourations and later develops rots and/or ferments resulting in the final softening of the root. This has restricted its availability, as there was always limited time to market. Cassava is still one of the more popularly consumed root crops in Trinidad and Tobago. Presently, there is a drive to increase its production in order to satisfy the local demand for fresh roots and reduce dependency on imports. This anticipated increased volume would require appropriate handling systems to facilitate high quality produce reaching the consumer. It is with this view, that this manual is prepared for existing and potential producers, handlers and extension workers.